Early Childhood Language Education and Literacy Practices in Ethiopia Perspectives from Indigenous Knowledge, Gender and Instructional Practices - Weldemariam, Kassahun; Sandvik, Margareth; Yigezu, Moges (Routledge Research in Language Education, 2024)
This edited volume explores how indigenous knowledges and practices can be instrumental in improving literacy outcomes and teacher development practices in Ethiopia, aiding children's long-term reading, and learning outcomes. The chapters present research from a collaborative project between Ethiopia and Norway and demonstrate how students can be supported to think pragmatically, learn critically and be in possession of the citizenship skills necessary to thrive in a multilingual world. The authors celebrate multilingualism and bring indigenous traditions such as oracy, storytelling, folktales to the fore revealing their positive impact on educational attainment. Addressing issues of language diversity and systematic ignorance of indigenous literacy practices, the book plays a necessary role in introducing Ethiopia's cultural heritage to the West and, hence, bridges the cultural gaps between the global north and global south. Arguably contributing one of the first publications on early literacy in Ethiopian languages, this book will appeal to scholars, researchers and postgraduate students studying the fields of early years literacy and language, indigenous knowledge and applied linguistics more broadly.